Continuous 1D single crystal growth with high aspect ratio by oriented aggregation of dendrite - Quan Wan; Maoqi Li; Yuhao Zhou; Meng Zhang; Zongpu Xu; Jie Wang; Yajun Shuai; Shuxu Yang; Mingying Yang (Communications Materials)
Abstract Continuous 1D growth of crystals is among one of the long-standing goals in material science. Classical generic methods for 1D crystal growth such as guided disposition restrict side growth by external bounding, and become difficult as the aspect ratio increases. Here, we find that continuous 1D growth of crystals can be achieved during dendrite formation, where the fractal dendrite crystal growth intrinsically restricts side broadening. We induce nanoparticle alignment in a solvent system with a polymer nanoparticle dispersion. This polymer additive further enabled an oriented aggregation mechanism during dendrite growth. The integration of these two mechanisms into the dendrite growth process regulates the dendrite shape. Such aggregated mono-crystalline dendrite branches can reach an ultra high aspect ratio (over 10000:1) with uniform diameter and orientation. We show an example application of such dendrite to prepare a high aspect ratio nanowire. This pathway may be extended for general 1D crystal growth system in the future.